An inventory model of purchase quantity for fully-loaded vehicles with maximum trips in consecutive transport time - Chen, P. (Yugoslav Journal of Operations Research, 2016)
Products made overseas but sold in Taiwan are very common. Regarding the cross-border or interregional production and marketing of goods, inventory decisionmakers often have to think about how to determine the amount of purchases per cycle, the number of transport vehicles, the working hours of each transport vehicle, and the delivery by ground or air transport to sales offices in order to minimize the total cost of the inventory in unit time. This model assumes that the amount of purchases for each order cycle should allow all rented vehicles to be fully loaded and the transport times to reach the upper limit within the time period. The main research findings of this study included the search for the optimal solution of the integer planning of the model and the results of sensitivity analysis.